Nurturing Youth Character Education Through the “Sungkem Pertiwi” Cultural Performance - Sawitri; Pujiyana; Suyahman (International Journal on Education Issues, 2026)
Purpose – This study aims to analyze the influence of cultural arts performances on the character education of the younger generation. Design/Methodology/Approach – The research employs a qualitative approach, focusing on performances by various art groups, including karawitan, Javanese poetry (gurit jawa), Indonesian poetry, wayang padat (concise puppet shows), and dance. Data were gathered from primary and secondary sources through in-depth interviews, literature reviews, photographic documentation, and observations of digital content on platforms such as YouTube and TikTok. Findings – The results indicate that cultural arts performances have a positive and significant impact on character education. Through performance themes such as "Sungkem Pertiwi," these artistic showcases serve as a platform for the nation's youth to contribute while instilling moral values, such as respect for parents and elders, and the philosophy of "humanizing human beings" (memanusiakan manusia). The sequence of artistic works cohesively provides character lessons encompassing aspects of tolerance, responsibility, and cooperation. Originality/Value –This research offers a unique contribution by examining the intersection of cultural art performances and character education, focusing on specific art forms such as karawitan, Javanese poetry, wayang padat, and traditional dance, which are often overlooked in contemporary educational discourse.